2011
DOI: 10.1039/c0ay00719f
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Total Organic Fluorine (TOF) in environmental samples using flow-injection and chromatographic methods

Abstract: Since the perfluorinated organic compounds have been recognized as persistent organic pollutants present in the environment, food and living organisms, new analytical methods are being developed for their determination. Many of the described earlier methods focus on determination of particular fluorinated compounds, however, the specific compounds are only a part of all organic fluorine compounds present in environmental or biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…The mass of unquantified organic fluorine is not unique; a study of surface water after a spill of fire retardant showed that the total mass of PFCs identified was significantly less than that the 19 F measured by NMR (Moody et al, 2001). There are other instances where for non-biological matrices EOF has occurred in significantly greater abundance than that identified by the commonly described PFCs (Trojanowicz et al, 2011). In comparison, EOF was 63% (n = 10) and 38% (n = 10) of TF, respectively, for two cetacean species .…”
Section: Tf and Eofmentioning
confidence: 98%
“…The mass of unquantified organic fluorine is not unique; a study of surface water after a spill of fire retardant showed that the total mass of PFCs identified was significantly less than that the 19 F measured by NMR (Moody et al, 2001). There are other instances where for non-biological matrices EOF has occurred in significantly greater abundance than that identified by the commonly described PFCs (Trojanowicz et al, 2011). In comparison, EOF was 63% (n = 10) and 38% (n = 10) of TF, respectively, for two cetacean species .…”
Section: Tf and Eofmentioning
confidence: 98%
“…The attempts to determine the released fluoride using flow-injection analysis methods with potentiometric and fluorimetric detections did not allow the obtaining a satisfactory LOD [92], hence chromatographic methods were employed for this purpose. In procedures of determinations of PFCAs in natural waters, the first stage is sorption of analytes on appropriate non-polar sorbent.…”
Section: Determination Of Total Organic Fluorine (Tof)mentioning
confidence: 99%
“…A – blank without SBP, B – blank after defluorination with SBP and derivatization with TPSiOH, C – PFOA standard solution after defluorination and derivatization, D – river water sample after defluorination and derivatization. b Comparison of TOF values determined by HPLC (white bars) in samples of natural waters with the content of individual PFASs identified and quantified by the LC/MS method [92]. KW – tap water from Warsaw, KT – tap water from city Tarnow (Poland) , W1 – river water from Vistula , T1 – surface water from Tarnow, Z – well water from Tarnow…”
Section: Determination Of Total Organic Fluorine (Tof)mentioning
confidence: 99%
“…For measurements of the diffusion coefficient the flow injection method [33,34] is used. The injection zone of the ligand in a cylindrical capillary has a shape of a small cylinder.…”
Section: Determination Of the Association Constant For Ligand-proteinmentioning
confidence: 99%